2017
DOI: 10.11648/j.cajph.20170303.11
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Rabies in and Around Lafia Metropolis, Nigeria

Abstract: Abstract:Rabies is endemic in Nigeria and other developing countries, killing 55,000 people annually. This descriptive cross-sectional study assessed the knowledge, attitudes and practices of rabies in and around Lafia, Central Nigeria. Semistructured questionnaires were administered to 200 consenting respondents from urban and sub-urban areas in Lafia. Of the 200 respondents, 76.5% heard of rabies with 89% and 64% from urban and sub-urban areas. There was no significant difference on the awareness of rabies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
3
2
Order By: Relevance
“…This is a better attitude than reports of other studies in Nigeria (Niger and Bauchi states) where only 28.1% and 35.4% of the dog bite victims received PEP from a health facility respectively [ 12 , 39 ]. This attitude was also consistent with the findings of Edukugbo et al [ 25 ] and Christopher et al [ 26 ]. Self-medication/treatment of bite wounds by some respondents may have been influenced by a low level of education, financial constraints, or ease and accessibility to a health facility.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is a better attitude than reports of other studies in Nigeria (Niger and Bauchi states) where only 28.1% and 35.4% of the dog bite victims received PEP from a health facility respectively [ 12 , 39 ]. This attitude was also consistent with the findings of Edukugbo et al [ 25 ] and Christopher et al [ 26 ]. Self-medication/treatment of bite wounds by some respondents may have been influenced by a low level of education, financial constraints, or ease and accessibility to a health facility.…”
Section: Discussionsupporting
confidence: 93%
“…This low awareness rate among the populace might be due to the lack of prioritization of rabies by the government and the lack of a state-wide or a national rabies control program in Nigeria. The rabies awareness rate in this study was very low compared to the 82% awareness rate reported in Abuja, Federal Capital Territory [25] as well as the 76.5% and 71.5% reported from Nasarawa state [26] and Taraba state [27] respectively. It is also lower than the awareness rates reported from other parts of the world.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The reason for this vulnerability is the likely nature of children will have animal affection. 9 Moreover, the age range 9–10 years is the appropriate starting point for knowledge and awareness education. 10 At this level of development, they can comprehend the issues (knowledge, attitude, and protection).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, rabies awareness surveys have been reported in Kaduna (Odeh et al, 2014), Nasarawa (Rine et al, 2017), Abia (Mshelbwala et al, 2014), and Zamfara State (Ijoma et al, 2021). KAP studies are particularly important to identify gaps in the knowledge, attitude or practices that could greatly impact the adoption of an intervention.…”
Section: Community Surveys Of Rabies Awarenessmentioning
confidence: 99%